2017
DOI: 10.1007/s40899-017-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

A combined pumping test and heat extraction/recirculation trial in an abandoned haematite ore mine shaft, Egremont, Cumbria, UK

Abstract: A pumping test at rates of up to 50 L s -1 was carried out in the 256 m-deep Florence Shaft of the Beckermet-Winscales-Florence haematite ore mine in Cumbria, UK, between 8th January and 25th March 2015. Drawdowns in mine water level did not exceed 4 m and the entire interconnected mine complex behaved as a single reservoir. Pumping did, however, induce drawdowns of around 1 m in the St. Bees Sandstone aquifer overlying the Carboniferous Limestone host rock. During a second phase of the pumping test, a proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…No system has been commissioned at the shaft, due to lack of clearly identified heat demand, and pending the demonstration of acceptable environmental impact, safe water disposal and agreement between owning/operating parties. Dissolved iron did not occur in significant amounts in the pumped water and no scaling or clogging issues were noted [58].…”
Section: The United Kingdommentioning
confidence: 97%
See 1 more Smart Citation
“…No system has been commissioned at the shaft, due to lack of clearly identified heat demand, and pending the demonstration of acceptable environmental impact, safe water disposal and agreement between owning/operating parties. Dissolved iron did not occur in significant amounts in the pumped water and no scaling or clogging issues were noted [58].…”
Section: The United Kingdommentioning
confidence: 97%
“…Open shafts provide access to a large volume of water in the mine workings and are engineered to remain open indefinitely [27], which brings extended life to the source. Hybrid systems are also possible, where part of the pumped water flow is returned to the shaft, while part is "bled off" and discharged to a surface recipient [58].…”
Section: Standing Columnmentioning
confidence: 99%
“…The larger (103 kW) pilot scheme at Egremont (Banks et al 2017) also successfully operated for a short trial period. However, monitoring of temperatures during the Egremont trial suggested that the heat extractable by a pure standing column arrangement might be limited to no more than 100 W m −1 (or several tens of kW for a typical deep mine shaft of several 100 m depth).…”
Section: Disadvantage: May Not Be Scaleablementioning
confidence: 99%
“…Egremont (Banks et al 2017) is based on an ironstone (haematite) mine, while the rest are coal mines…”
Section: Introduction: Mine Water As a Thermal Resourcementioning
confidence: 99%